The effect of group investigation model of learning on improving mathematics learning outcomes - Kuratul Aini; Mahsup Mahsup; Vera Mandailina; Abdillah Abdillah; Putri Ayu Febriani (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
The instructional model is a crucial component in the educational process. This study evaluates the effectiveness of the Group Investigation learning model in enhancing students' mathematics outcomes. A quantitative research method with a One Group Pretest-Posttest design was used, involving 29 eighth-grade students. Data were analyzed using SPSS version 25, revealing a pretest score of 0.010 and a posttest score of 0.063 after implementing the Group Investigation model. The average posttest score was 77.91, indicating a significant impact on learning outcomes. Observations over three sessions showed an increase in student participation from 26.97% with an average score of 2.24 in Session I (categorized as "Less Active") to 42.79% with an average score of 3.56 in Session II, and 45.38% with an average score of 3.78 in Session III (both categorized as "Active"). This increase demonstrates that the Group Investigation model not only enhances student participation but also makes students more active in learning, thereby improving mathematics outcomes. Therefore, the Group Investigation model is an effective strategy for enhancing students' achievement in mathematics. Further research with more refined methods and tools is needed to confirm these findings.